If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 36 = (8) + -1(14x) 36 = 8 + -1(14x) Remove parenthesis around (14x) 36 = 8 + -1 * 14x Multiply -1 * 14 36 = 8 + -14x Solving 36 = 8 + -14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14x' to each side of the equation. 36 + 14x = 8 + -14x + 14x Combine like terms: -14x + 14x = 0 36 + 14x = 8 + 0 36 + 14x = 8 Add '-36' to each side of the equation. 36 + -36 + 14x = 8 + -36 Combine like terms: 36 + -36 = 0 0 + 14x = 8 + -36 14x = 8 + -36 Combine like terms: 8 + -36 = -28 14x = -28 Divide each side by '14'. x = -2 Simplifying x = -2
| 0.05m=13.80 | | 9.2=-5g-23.3 | | (-3x)-(7)=23 | | 65-x=180 | | 9+2x=49 | | (-3x)-(7)=3 | | [5x]-7=14 | | abs(5x-4)=-6 | | 9x-4=72 | | 15m+6.3=9.8 | | abs(5x-4)=6 | | Y=7.5+0.5x | | 12y=-48+4x | | 4+12x=112 | | 2(3x+1)-x=3 | | B-(2)=-11 | | 14-4y=y+x | | 1n+3-1=8 | | y-34=41/11(20-6) | | 3x-24=2x+26 | | y-34=41/11(18-6) | | 14x^2+9x=-1 | | -4+6(x-4)=15x+2-9x | | y-4/3-7=.25 | | 6n+3(n+2)=-(2n+7)+n | | -6m=42 | | 5x(2x+7)=2 | | 14x-8=34 | | 6-y/(-1)=0 | | 11-(3v+5)=3v-6 | | .15x=23 | | 3w+6-w=5w-2(w-3) |